IMPLEMENTASI PENILAIAN AUTENTIK PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI - Riri Susanti (IAIN Batusangkar, 2016)
The problem in this study was the lack of understanding on the authentic assessment of teachers according to the curriculum 2013. This study aimed at describing the planning and the implementation of authentic assessment according to the curriculum 2013 in Elementary School 21 Batubasa. This research was a qualitative research. Data collection methods used in this research were the study of documents, observation, and interview. Data were analyzed by using descriptive analysis. The subjects used in this research was Islamic education teachers in Elementary School 21 Batubasa. The results showed that (1) the planning of authentic assessment in Islamic Education and Character Subject of Elementary School 21 Batubasa was good category; and (2) the implementation of authentic assessment was not perfect. This research concluded that the authentic assessment according to the curriculum 2013 in Islamic Education and Character Subject of Elementary School 21 Batubasa was run well but it got some obstacles in its implementation.Keywords: Authentic Assessment, Islamic Education, Curriculum 2013, Elementary School, Batubasa